EFFECT OF FARM INCOME ON THE LIFESTYLE FACTORS OF FARMERS IN KWARA STATE, NIGERIA - Oluwaremilekun A. ADEBISI; Luke O. ADEBISI; Olufunke T. OLUDARE; Temitope O. DAODU; Marvellous T. OWOLABI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The rising occurrence of chronic and cardiovascular diseases has brought awareness to the role that lifestyle factors play in an individual’s disease risk. This study investigated the effect of income from farming on the lifestyle factors of farmers utilizing cross-sectional data gathered from 150 farmers across Kwara State, Nigeria. Three stage random sampling was utilized and the data were analyzed using Descriptive statistics, Simple Lifestyle Indicator Questionnaire and Tobit regression model. The study uncovered that 63.33% of the farmers in the investigated region practiced unhealthy lifestyles while the Tobit regression model result revealed five out of nine independent variables (namely gender, age, educational level, farm size and farm income (the variable of concern)) included in the model were discovered to be significant factors affecting lifestyle factors in the investigated region. The research therefore concluded that farm income has effect on the lifestyle factors of farmers in the study area. Howbeit, the study recommends that farmers should be sensitized on health education so as to understand the pros and cons to various lifestyle factors practiced in order for them to be more cautious regarding their health.